Longitudinal Evaluation of Cerebellar Signs of H-ABC Tubulinopathy in a Patient and in the taiep Model - Alata, Milvia; González-Vega, Arturo; Piazza, Valeria; Kleinert-Altamirano, Anke; Cortes, Carmen; Ahumada-Juárez, Juan C.; Eguibar, Jose R.; López-Juárez, Alejandra; Hernandez, Victor H. (Frontiers in Neurology, 2021)
H-ABC is a central neurodegenerative disease due to mutations in the TUBB4A gene, characterized by motor development delay, abnormal movements, ataxia, spasticity, dysarthria, and cognitive deficits. Diagnosis is made by integrating clinical data and radiological signs. Differences in MRIs have been reported in patients that carry the same mutation, however a quantitative study has not been performed so far. Our study aimed to provide a longitudinal analysis of the changes in the cerebellum, corpus callosum, ventricular system, and striatum in a patient suffering from H-ABC and in the taiep rat. We analyzed the rat gait, performed immunofluorescence, and segmentation of cerebellum, corpus callosum, and ventricular system, comparing the changes in their volumes. We found that cerebellar and callosal hypomyelination worsened with age, in concomitance with the emergence of ataxic gait in the rat. This hypomyelination in H-ABC is progressive and can be involved in the clinical deterioration. Also a progressive lateral ventriculomegaly was observed in both patient and taiep, which could be secondary to the atrophy of the white matter. H-ABC gives rise to a spectrum of clinical signs whose pathophysiology still needs to be understood.